2020
DOI: 10.1038/s41598-020-71171-y
|View full text |Cite
|
Sign up to set email alerts
|

An altered glial phenotype in the NL3R451C mouse model of autism

Abstract: Autism Spectrum Disorder (ASD; autism) is a neurodevelopmental disorder characterised by deficits in social communication, and restricted and/or repetitive behaviours. While the precise pathophysiologies are unclear, increasing evidence supports a role for dysregulated neuroinflammation in the brain with potential effects on synapse function. Here, we studied characteristics of microglia and astrocytes in the Neuroligin-3 (NL3 R451C) mouse model of autism since these cell types are involved in regulating both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
(78 reference statements)
2
14
0
Order By: Relevance
“…Moreover, we also observed an increase in the amount of activated microglia in different brain regions of CD animals, which was prevented by treatment. Interestingly, alterations in activated glia density have also been observed in other mice models for different neurodevelopmental diseases (Lee et al, 2019;Matta et al, 2020). Curcumin has been previously related with the increase of Nrf2 expression and nuclear translocation (Tapia et al, 2012;Fattori et al, 2015), suggesting that this endogenous antiinflammatory pathway is modulating this response in CD animals, which correlates with similar findings in this model (Ortiz-Romero et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, we also observed an increase in the amount of activated microglia in different brain regions of CD animals, which was prevented by treatment. Interestingly, alterations in activated glia density have also been observed in other mice models for different neurodevelopmental diseases (Lee et al, 2019;Matta et al, 2020). Curcumin has been previously related with the increase of Nrf2 expression and nuclear translocation (Tapia et al, 2012;Fattori et al, 2015), suggesting that this endogenous antiinflammatory pathway is modulating this response in CD animals, which correlates with similar findings in this model (Ortiz-Romero et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…The role of Nlgn1-3 proteins in astrocyte morphogenesis differs in an isoform-and time-dependent manner (Stogsdill et al, 2017). Additionally, the Nlgn3-R451C mutation affects astrocytic morphology by reducing their branch point number, branch length, and territory in the dentate gyrus (Matta et al, 2020). Furthermore, oligodendrocytic Nlgn3 protein contributes to the differentiation of oligodendrocytes (Proctor et al, 2015) and the density of microglia is increased in the dentate gyrus of Nlgn3-R451C KI mice (Matta et al, 2020).…”
Section: Functions Of Nlgn3 In Non-neuronal Cells and Outside The Cns Nlgn3 In Glial Cellsmentioning
confidence: 99%
“…Additionally, the Nlgn3-R451C mutation affects astrocytic morphology by reducing their branch point number, branch length, and territory in the dentate gyrus (Matta et al, 2020). Furthermore, oligodendrocytic Nlgn3 protein contributes to the differentiation of oligodendrocytes (Proctor et al, 2015) and the density of microglia is increased in the dentate gyrus of Nlgn3-R451C KI mice (Matta et al, 2020). Interestingly, glial progenitor cells from individuals with schizophrenia express significantly lower levels of Nlgn1, Nlgn2, and Nlgn3 mRNA compared with controls (Windrem et al, 2017), suggesting a role for glial Nlgn3 protein in pathophysiological conditions.…”
Section: Functions Of Nlgn3 In Non-neuronal Cells and Outside The Cns Nlgn3 In Glial Cellsmentioning
confidence: 99%
“…Codagnone and colleagues (2015) showed that VPA exposed rats, sacrificed at postnatal day 35, have increased glial fibrillary acid protein (GFAP) immunostaining levels in the medial prefrontal cortex and hippocampus, especially in the CA3 subfield. Despite increased GFAP immunoreactivity, which is often associated with pathological processes in the CNS, there are some studies showing changes in the number of GFAP positive cells in VPA and poly (I:C) models [ 93 , 94 , 95 , 96 ], but studies regarding the morphological analysis of glia silhouette in autism are limited [ 11 , 13 ]. Given the still growing knowledge about the pivotal role of those “shape changes” for proper neuronal functioning, a lack of profound morphological analysis of these cells in ASD is quite surprising.…”
Section: Astrocytes In Asd—insights From the Clinical Cases And Preclinical Modelsmentioning
confidence: 99%
“…The differences may be due to the difficulty of accessing human tissue and the inadequate processing of the tissue prior to staining. Disruption in glial markers expression in ASD coincides with pathological changes of neurons within brain structures associated with social behaviour, reward, attention or cognitive processes (i.e., prefrontal cortex, hippocampi, striatum, amygdala, cerebellum) [ 10 , 11 ]. Lack of appropriate support from glia cells may be the cause of neuronal or synaptic connection alterations which may lead to the occurrence of neuropsychiatric disorders such as autism.…”
Section: Introductionmentioning
confidence: 99%